2018
DOI: 10.7441/joc.2018.04.04
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of Perceived Business Risks on the Size of SMEs

Abstract: The issues of risk management in small and medium-sized enterprises (SMEs) have been analysed and discussed for a long time. Nevertheless, it is still necessary to concentrate on this field, especially in the Slovak Republic. SMEs are very sensitive to changes in the business environment which are always reflected in the quantitative characteristics of this sector in a certain time interval. According to various global surveys and studies, risk management represents a significant contribution to the increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 32 publications
(36 reference statements)
4
39
0
Order By: Relevance
“…The research has confirmed that unpreparedness for specific risks that may arise in China can have unfortunate economic consequences, this corresponding to the outcomes of a broader study by Hudakova et al (2018).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The research has confirmed that unpreparedness for specific risks that may arise in China can have unfortunate economic consequences, this corresponding to the outcomes of a broader study by Hudakova et al (2018).…”
Section: Resultssupporting
confidence: 60%
“…Corporate management's ability to work with risk is the subject of research in many countries. Recent study conducted by Hudakova et al (2018), for example, follows up on similar research carried out in the Czech Republic, Poland, Hungary and Serbia. A considerable number of risk management models generate a range of studies and manuals dealing with the issue; the following selection lists just a few examples -Alma (2017); Brillinger (2018); Dostál et al (2005); Fotr & Hnilica (2014); Korecký & Trkovský (2011); Valaskova et al (2018).…”
Section: Coping With Riskmentioning
confidence: 99%
“…One of the reasons for this is, undoubtedly, the sensitivity of this type of enterprise to changes in the business environment. The research conducted by Hudakova et al (2018) shows that among enterprises in the SMEs sector in the Slovak Republic, market, financial, economic and personal risks are the main ones that affect negatively the business environment of small and medium-sized enterprises. The authors also indicate that to improve the level of risk management, it is necessary to increase theoretical knowledge about it among entrepreneurs, as well as to familiarize them with methods and tools that can be used in risk management processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If economic institutions contribute to the explanation of opportunity entrepreneurship, then it can be assumed that they may predict business risk. Thus, doing business in an unstable economic environment may lead the business to expose themselves to business risk (Hudakova, Masar, Luskova, & Patak, 2018;Martinez, Zouaghi, Marco, & Robinson, 2019). Scholars have shown that macroeconomic environment affects business performance leading to the failure of businesses (Karabag, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%